2019
DOI: 10.1016/j.ihj.2019.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-month comparative analysis of clinical outcomes using biodegradable polymer–coated everolimus-eluting stents versus durable polymer–coated everolimus-eluting stents in all-comer patients

Abstract: Aim The purpose of the present study was to examine whether clinical differences exist between the biodegradable polymer (BDP)–coated Tetrilimus everolimus-eluting stent (EES) and the durable polymer (DP)–coated Xience EES by comparing the major adverse cardiac event (MACE) rate at 12 months in all-comer patients. Methods This study was designed as a multicentre, observational, retrospective, investigator-initiated study between January 2016 and October 2016. Two hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…In addition to ultrathin platform of Tetrilimus EES, its unique biodegradable polymer-coating, novel LDZ-link (making it more flexible and deliverable) and wide range of available size matrix (making it suitable for small vessels [<2.5 mm] as well as long lesions [>40 mm]) demonstrates favorable long-term safety and effectiveness as reported in the current and in the previous studies. 14 , 15 , 16 , 17 , 18 , 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to ultrathin platform of Tetrilimus EES, its unique biodegradable polymer-coating, novel LDZ-link (making it more flexible and deliverable) and wide range of available size matrix (making it suitable for small vessels [<2.5 mm] as well as long lesions [>40 mm]) demonstrates favorable long-term safety and effectiveness as reported in the current and in the previous studies. 14 , 15 , 16 , 17 , 18 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…Tetrilimus (Sahajanand Medical Technologies Ltd., Surat, India), an everolimus-eluting stent (EES), is a latest generation DES with biodegradable polymer-coating on an ultrathin (60 μm) cobalt-chromium platform with unique long-dual Z (LDZ) link connectors. The safety and effectiveness of Tetrilimus EES have previously been reported in several studies, 14 , 15 , 16 , 17 , 18 but there are inadequate long-term clinical data (>1 year after implantation) on this latest generation ultrathin DES. 19 Specifically, there is a need to establish whether Tetrilimus EES can overcome the limitations of earlier generation DES, like late in-stent restenosis and very late stent thrombosis.…”
Section: Introductionmentioning
confidence: 97%
“…Recent decades have seen dramatic growth in stent innovation and the manufacturing of indigenous coronary stents with biodegradable polymers. Various studies have shown the feasibility and efficacy of these stents individually [16][17][18][19][20][21][22]26]. However, there is a scarcity of literature regarding the real-life experience related to these stents outside of trial settings, especially outcome analysis with these stents examined together.…”
Section: Discussionmentioning
confidence: 99%
“…Various Indian manufacturers produce biodegradable or polymer-free stents that are widely used across the world. The safety and efficacy of these Indian stents have been established in well-structured clinical trials [15][16][17][18][19][20][21][22]. However, there is a scarcity of data and evidence related to their safety and efficacy in the real-world or clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…The 12-mo MACE rate following implantation of EES ranged from 0.3% to 6.2% for diverse clinical presentations in randomized trials, and real-world studies[ 19 - 24 ]. The 1-year incidence of MACE following treatment with another indigenous biodegradable polymer DEC ranged from 0.9% to 4.2%[ 25 - 27 ]. No MACE was reported during the 1-year follow-up period in our study.…”
Section: Discussionmentioning
confidence: 99%